Driving performance at the National Transportation Safety Committee: The mediating role of engagement and motivation in transformational leadership - Cris Kuntadi; Winda Widyanty; R. Nurhidajat; Martha Fani Cahyandito; Pungki Sariadi; Mochammad Fahlevi (Cogent Business & Management, 2023)
This study aims to analyze the influence of transformational leadership on the employee performance of National Transportation Safety Committee (NTSC) with the mediating role of work engagement and work motivation. The study employed a census approach utilizing structural equation modeling (SEM) to analyze the data collected from all employees of the NTSC in Indonesia. Primary data were gathered through a comprehensive questionnaire, which was administered to the entire population of 107 NTSC employees, ensuring complete coverage and representation. The results of this study indicate that transformational leadership has a positive and significant effect on work engagement, work motivation, and employee performance. The results show that work engagement and work motivation have a positive and significant effect on employee performance. While the mediation test results show that work engagement and work motivation have an indirect effect on employee performance. The current study provides fresh insights and validates extant knowledge on transformational leadership, work engagement, work motivation and employee performance within the NTSC. This study suggests NTSC management to communicate the company's vision and mission to employees with openness and realize improvements in operational standards so that the performance created in the organization provides value that can be understood appropriately. In addition, management also needs to create policies that are in line with the NTSC vision and mission.
Keywords: 650; employee performance; National Transportation Safety Committee; transformational leadership; work engagement; work motivation